Guest Editorial: Ignoring the Social and Cultural Context of Bioethics Is Unacceptable - Fox, Renée C. (Cambridge quarterly of healthcare ethics, 2010)
To quote Yogi Berra, writing this editorial is a “déja vu all over again” experience for us. It entails not only collaborating once more as coauthors but also reiterating some of the criticisms and concerns that have figured prominently in virtually all our previous publications about bioethics—most recently in our book Observing Bioethics.